Coastal Bacterioplankton Metabolism Is Stimulated Stronger by Anthropogenic Aerosols than Saharan Dust - Marín, Isabel; Nunes, Sdena; Sánchez-Pérez, Elvia D.; Txurruka, Estibalitz; Antequera, Carolina; Sala, Maria M.; Marrasé, Cèlia; Peters, Francesc (Frontiers in Microbiology, 2017)
In oligotrophic regions, such as the Mediterranean Sea, atmospheric deposition has the potential to stimulate heterotrophic prokaryote growth and production in surface waters, especially during the summer stratification period. Previous studies focused on the role of leaching nutrients from mineral particles of Saharan origin, and were restricted to single locations at given times of the year. In this study, we evaluate the effect of atmospheric particles from diverse sources and with a markedly different chemical composition (Saharan dust and anthropogenic aerosols) on marine planktonic communities from three locations of the northwestern Mediterranean with contrasted anthropogenic footprint. Experiments were also carried out at different times of the year, considering diverse initial conditions. We followed the dynamics of the heterotrophic community and a range of biogeochemical and physiological parameters in six experiments. While the effect of aerosols on bacterial abundance was overall low, bacterial heterotrophic production was up to 3.3 and 2.1 times higher in the samples amended with anthropogenic and Saharan aerosols, respectively, than in the controls. Extracellular enzymatic activities (leu-aminopeptidase and ß-glucosidase) were also enhanced with aerosols, especially from anthropogenic origin. Leu-aminopeptidase and ß-glucosidase increased up to 7.1 in the samples amended with anthropogenic aerosols, and up to 1.7 and 2.1 times, respectively, with Saharan dust. The larger stimulation observed with anthropogenic aerosols might be attributed to their higher content in nitrate. However, the response was variable depending the initial status of the seawater. In addition, we found that both anthropogenic and Saharan aerosols stimulated bacterial abundance and metabolism significantly more in the absence of competitors and predators.